Pengaruh Online Customer Review, Online Customer Rating, dan Metode Pembayaran Cash on Delivery (COD) terhadap Keputusan Pembelian Konsumen di Tiktok Shop (Studi Kasus Pada Mahasiswa FEB Unisma Malang Angkatan 2019) - Elviana Dwi Firdaus; N Rachma; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of Online Customer Reviews, Online Customer Ratings and the Cash on Delivery (COD) Payment Method on consumer purchasing decisions at Tiktok Stores with a case study of students from the Faculty of Economics and Business Class of 2019 at the Faculty of Economics and Business, Islamic University, University of Malang. 105 samples were distributed using the Malhotra formula. The method used is a quantitative method with an Explanatory Research approach. This research uses primary data with a questionnaire technique. For data processing used multiple linear regression analysis method. The results of this study indicate that Online Customer Reviews and the COD payment method have a significant effect on purchasing decisions. Meanwhile, Online Customer Rating has no significant effect on purchasing decisions. Keywords: Online Customer Reviews, Online Customer Ratings, Cash on Delivery Payment Methods, Purchasing Decisions